Market access and plant biosecurity initiatives and strategies for making Indian farming remunerative - Susheela, K; Madhubala, R; Sujeetha, Alice R P (Indian Journal of Plant Protection, 2020)
India is a front runner in the production of many agricultural commodities including fruits and vegetables in world. Though the production is commendable, the export of fresh agricultural products from India is negligible, due to many problems. On the other hand, increased global trade in agriculture leads to introduction of many exotic pests. This review takes stock of the situation and draws road map to employ the export promotion activities and strengthen the plant biosecurity to avoid the entry of exotic pests. The initiatives and strategies such as market access for export promotion, establishment of pest free areas, domestic plant quarantine, certification for pathogen free seeds/planting materials, good agricultural practices need to be strengthened for safe export. At the same time, India has to be safeguarded from the ravages of exotic plant pests by strengthening the areas such as exotic plant pest alerts, exotic pest surveillance, plant pest emergency preparedness, pest incursion management, regional cooperation and public awareness on exotic species. The government’s vision of doubling farmers’ income and make farming remunerative can be achieved by applying these initiatives and strategies in relation to market access for export promotion and plant biosecurity to prevent entry of exotic pests.